2005
DOI: 10.1093/ndt/gfh744
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of Ras GTPase isoforms in normal human kidney

Abstract: Ras isoforms have distinct and separate subcellular distributions in normal kidney cells. Understanding the functional aspects of this distribution pattern is essential if Ras is to be targeted by genetic or molecular therapeutic tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Subcellular localization of a protein often provides important clues to its function [20], and the transition from the benign state to the fully malignant one might involve a change in subcellular presence. As accumulating evidence has indicated that in many cancers the heterogeneous subcellular distribution and translocation of important cancer-related proteins, that is, Ras GTPase isoforms [21], cyclin D1 [22], p27 Kip1 [23], and chloride intracellular channel 4 [24], in tumor sites are associated with tumor characteristics and clinical outcome, and cause the loss and gain of function in essential activities, such changes are a new paradigm in sorting out changes that are relevant to malignant transformation. Thus, it would seem that alteration of the subcellular localization of ATG16L1 protein may contribute to the malignant phenotype of OSCC cells and could be a relevant event in oral carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular localization of a protein often provides important clues to its function [20], and the transition from the benign state to the fully malignant one might involve a change in subcellular presence. As accumulating evidence has indicated that in many cancers the heterogeneous subcellular distribution and translocation of important cancer-related proteins, that is, Ras GTPase isoforms [21], cyclin D1 [22], p27 Kip1 [23], and chloride intracellular channel 4 [24], in tumor sites are associated with tumor characteristics and clinical outcome, and cause the loss and gain of function in essential activities, such changes are a new paradigm in sorting out changes that are relevant to malignant transformation. Thus, it would seem that alteration of the subcellular localization of ATG16L1 protein may contribute to the malignant phenotype of OSCC cells and could be a relevant event in oral carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mutants in the RAS2 gene have been isolated as suppressors of mutants in genes encoding subunits of the mitochondrial ATP synthase (Mabuchi et al, 2000). Finally, it may be recalled that some reports of mitochondrial localization of Ras have been published, although their functional significance remains to be seen (Rebollo et al, 1999;Kocher et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the human kidney, H-Ras localizes with mitochondria in proximal and distal convoluted tubules (30). Bcl-2 and Ras proteins interact at mitochondria in the murine T-cell line TS1␣ß, and the mitochondrial association of the three Ras proteins is differentially regulated by interleukin-2 supplementation (48).…”
Section: Discussionmentioning
confidence: 99%